Analysis of Student Engangement and Perceptions of Community of Inquiry (CoI)-based Blended Learning in The Chemical Separation Subject on Chromatography - Agita Dzulhajh Anggraini; Surjani Wonorahardjo; Yudhi Utomo (Jurnal Pendidikan Sains, 2023)
Learning in higher education has often been conducted solely through face-to-face, teacher-centered approaches. Implementing Community of Inquiry (CoI)-based blended learning in chromatography is crucial as it offers students a novel learning experience. This pre-experimental study, utilizing a one-group pretest-posttest design, aimed to describe students’ perceptions of CoI-based blended learning in chromatography. Data were collected using a questionnaire comprising 34 statements. The results indicated that students had a neutral perception of CoI-based blended learning. While a community of inquiry has been established, it has not yet reached its full potential, as students have not fully experienced social presence in the learning process.DOI: 10.17977/jps.v11i32023p117